Thuật toán Systolic cho các phép toán cơ sở dữ liệu quan hệ - Ban, Đoàn Văn; Thuần, Nguyễn Ngọc (Journal of Computer Science and Cybernetics, 2016)
In this paper we present some systolic algorithms for performing relational database operations, including Cartesian product, join, and sorting. They operate in a parallel and pipelined fashion. Their time complexity is linear in terms of the number of tuples involved. Because of the regularity of their structures, they are most suitable for VLSI implementation.